The Role of Intellectual Capital To Economic Value Added (Empirical Study on Manufacturing Companies of Consumption Goods Sector) - Masri, Indah; Frisca, Dinda Putri; Satria, Indra; Bantasyam, Sofyan (Jurnal ASET (Akuntansi Riset), 2018)
The purpose of this study to analyze the influence of Intellectual Capital to Economic Value Added. The samples are 90 manufacture companies as the item of observations that were taken from annual reports listed of Indonesian Stock Exchange in 2011-2015. The model that used to measure intellectual capital was using Modified Value Added Intellectual Capital Coefficient (M-VAIC). M-VAIC component consist of Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Capital Employed Efficiency (CEE) and Relational Capital Efficiency (RCE). This research is quantitative research and using panel data regression on balanced data of fixed effect for data analysis. The results showed that Human Capital Efficiency (HCE) and Structural Capital Efficiency (SCE) has no positive impact on Economy Value Added (EVA) but in this research has a positive impact on the Capital Employed Efficiency (CEE) and Relational Capital Efficiency (RCE) to Economic Value Added (EVA).